The effect of butaselmevit and closaverm A on the immune status of cows with experimental fasciolosis sensitized by atypical mycobacteria : ст. - Kuljaba, O. V.; Stybel, V. V.; Gutyj, B. V.; Peleno, R. A.; Semaniuk, V. I.; Semaniuk, V. I.; Pryima, O. B.; Mazur, I. Ya.; Turko, I. (Львівський національний університет ветеринарної медицини та біотехнологій імені С. З. Гжицького, 2022)
There are many reports in the literature about the critical role of the immune system in protecting the body against foreign agents. However, the role of immune status in the association of mycobacteriosis and fasciolosis has not been studied. The work aimed to investigate the effect of butaselmevit and closaverm A on the immune status of cows with experimental fasciolosis sensitized by atypical mycobacteria. For the trial, 15 cows of 4–5 years of age, black and spotted breed, were selected, from which 3 groups were formed, five animals in each. Cows of the first research group for experimental fasciolosis were injected intramuscularly with closaverm A at a dose of 0.5 ml of the drug per 10 kg of body weight. The animals of the second experimental group, for experimental fasciolosis, were intramuscularly injected with closaverm A at a dose of 0.5 ml of the drug per 10 kg of body weight and butaselmevit at a dose of 10 ml of the drug per animal. The obtained results indicate that the drugs “Klosaverm A” and “Butaselmevit” when administered intramuscularly to cows with experimental fasciolosis, sensitized by atypical mycobacteria, contribute to the activation of cellular and nonspecific links of immunity. It should be noted that a number of our research also established the stimulating effect of drugs on the humoral link of immunity, in particular, an increase in the bactericidal and lysozyme activity of blood serum of cows associated with mycobacteriosis and fasciolosis. Using “Klosaverm A” and “Butaselmevit” drugs in experimental groups of animals helped reduce the level of CIC to physiological values starting from the 21st day of the experiment. It should be noted that according to the indicators of the immune system in cows with experimental fasciolosis, sensitized by atypical mycobacteria, the combined use of closer A and butaselmevit shows a better therapeutic effect than the use of only closaverm A alone.
Keywords: cows; butaselmevit; closaverm A; atypical mycobacteria; атипові мікобактерії; бутазельмевіт; клосаверм А; корови